Selective Recording of Tectonic Forcings in an Oligocene/Miocene Submarine Channel System: Insights From New Age Constraints and Sediment Volumes From the Austrian Northern Alpine Foreland Basin - Hülscher, Julian; Fischer, Gero; Grunert, Patrick; Auer, Gerald; Bernhardt, Anne (Frontiers in Earth Science, 2019)
Detailed characterization of variations in sediment architecture, flux, and transport processes in peri-orogenic basins offers insights into external climatic or tectonic forcings. We tested how four well-known tectonic/erosional events in the Oligocene/Miocene Alpine source area are recorded in the sediment-accumulation rates (SARs) of the deep marine sink in the Northern Alpine Foreland Basin (NAFB): exhumation of the Lepontine Dome (starting at 30 Ma) and the Tauern Window (23-21 Ma), erosion of the Augenstein Formation (∼21 Ma), and the visco-elastic relaxation of the European Plate. The Upper Austrian NAFB offers a unique opportunity to investigate external forcings on sedimentary infill due to the large amount of data on the Alpine hinterland and foreland. Deep-marine sedimentation, forming the Puchkirchen Group and the basal Hall Formation, was controlled by a basin-axial submarine channel (3–5 km wide, >100 km length). Two basin-wide unconformities were recognized in seismic-reflection data: the Northern Slope Unconformity (NSU) and the Base Hall Unconformity (BHU). We combine biostratigraphic and chemostratigraphic analyses of 316 drill-cutting samples from three wells with a large 3D-seismic-reflection data set (3300 km2, >5 km depth) to determine age and duration of the unconformities and to calculate spatially averaged SARs for the submarine channel and its overbanks, separately. Deepening of the basin, recorded by the NSU, occurred between 28.1 and 26.9 Ma. The Puchkirchen Group (26.9–19.6 Ma) is characterized by constant SARs (within standard deviation) in the channel [432–623 (t/m2/Ma)] and on the overbanks [240–340 (t/m2/Ma)]. The visco-elastic relaxation of the European Plate results in low SARs on the overbanks [186 (t/m2/Ma)], a decrease in sediment grain size in channel deposits and a decrease in sea level at the BHU (19.6–19.0 Ma). In the upper Hall Formation (19.0–18.1 Ma), clinoforms prograding from the south filled up the basin [1497 (t/m2/Ma)] within 1 Myrs. We conclude that only two of the tectonic signals are recorded in this part of the deep-marine sink, erosion of Augenstein Formation and visco-elastic relaxation of the European Plate; the exhumation of the Tauern Window and Lepontine Dome remain unrecorded.